Streptococcus canis transcriptomic modifications in host cell entry environments of human keratinocytes - Haruno Yoshida; Mieko Goto; Yuzo Tsuyuki; Jae-Seok Kim; Takashi Takahashi (BMC Genomics)
Abstract Background Streptococcus canis is a commensal bacterium in companion animals. This microorganism can infect humans who have been in deep contact with or bitten by pet dogs, suggesting that the skin/soft tissue is one of infection entry sites. To understand pathological process in human cells, we aimed to determine S. canis transcriptomic changes in invasive environments of human keratinocytes. Methods We selected one isolate from candidates with whole-genome sequences, based on re-obtained cell invasion ability (CIA) data into human keratinocytes along with bacterial cytotoxicity. RNA-sequencing was conducted for the samples at baselines and 2 h/5 hr post-inoculation using NovaSeq 6000. Global/differential gene expression analyses [principal component analysis (PCA)/k-means clustering analysis/differentially expressed gene (DEG) analyses] were performed. We classified DEGs into their functional categories. To validate transcriptomic results, we did quantitative reverse transcription-polymerase chain reaction (qRT-PCR) assays. Results FU1 isolate was selected from seven candidates, based on re-obtained CIA data with less cytotoxicity. Total read bases of 6.17–9.02 Gbp were obtained by RNA-sequencing. PCA and k-means clustering analysis indicated clustering according to their inoculation times. Volcano plots and Venn diagrams revealed that S. canis invasion into keratinocytes produced altered distributions of many genes. Gene ontology enrichment analysis showed most of the gene expressions were downregulated. DEG functional analysis showed the downregulated DEGs belonging to energy production and conversion/carbohydrate transport and metabolism/amino acid transport and metabolism/nucleotide transport and metabolism, with the upregulated DEGs belonging to transcription. qRT-PCR assays for downregulated/upregulated expressions of four genes (pgk–slo/opuAA–kdpB) validated transcriptomic results. Conclusion Our observations suggest that S. canis can downregulate its metabolism-associated gene expressions in human keratinocyte environments. The observed gene expression changes can imply the latent infection in human cells. Further investigation is needed to elucidate the underlying mechanisms for the latent infection.